Facile synthesis of a novel Zn₂Ti₃O₈ aerogel with porous structure for high-efficient degradation of antibiotics under simulated sunlight - Yuan, Meiyu (2023)
Photocatalytic degradation, as advanced oxidation methods with high efficiency and good stability, is considered a promising method to alleviate antibiotic pollution. Herein, we prepared a novel Zn2Ti3O8 aerogel by a simple sol-gel method based on the advantages of the abundant pore structure of aerogel material and the high photocatalytic activity of zinc titanate. The Zn2Ti3O8 aerogel shows a typical homogeneous structure and low band gap width (3.32 eV), which could achieve photogenerated carrier separation and transfer under simulated sunlight. The material has high specific surface area (120.1 m2/g) and abundant pore structure, which can provide multiple diffusion channels for pollutant molecules and generate massive reactive sites. In the absence of cocatalysts, the prepared Zn2Ti3O8 aerogel can achieve more than 95% degradation efficiency for 50 mg/L of ofloxacin (OFL) contaminated solution in 60 min. Electrochemical impedance spectroscopy (EIS) and transient photocurrent test results display that Zn2Ti3O8 aerogel exhibits the highest photocurrent density and lower charge transfer resistance. Meanwhile, the results of density functional theory (DFT) are consistent with the characterization results of electron spin resonance (ESR). The ·OH and ·O2− generated in the catalytic reaction could attack OFL molecules from different regions to achieve the purpose of decomposition. We believe that the as-prepared Zn2Ti3O8 aerogels are expected to be used in the practical treatment of catalytic degradation of OFL and other antibiotic pollutants.